Strenght parameters of compacted cohesive soils: analysis of sandy-clayely soils of the “Lisciani di Pantalla” (Todi – central Italy) - Di Matteo, Lucio; Brunelli, Simone; Capponi, Enrico (Italian journal of engineering geology and environment, 2008)
An experimental investigation was made on the mechanical behavior of mixtures constituted by sand (SW) and clayey silt (CL), in relation to dry density. The materials analyzed are from “Lisciani di Pantalla,” a locality in Umbria situated between Perugia and Todi (Central Italy). The results of the consolidated drained direct shear tests showed that the mixtures analyzed have maximum cohesion for a dry density values less than maximum dry density. The angle of internal friction, at least for the dry side of the Proctor curve, has a maximum at the maximum dry density. For mixtures with a high fine fraction content (CL = 60%), a small reduction in dry density produces a more than 50% increase in cohesion and about a 40% reduction in the angle of internal friction. At the optimum condition of compaction the angle of internal friction decreases with the increase in the clayey silt content, going from 43° to 32°. Under the same conditions, cohesion takes on values between 16 and 24 kPa, being lower for a CL content of 60% than one of 35%, showing a maximum between these two content percentages. The results obtained not only increase knowledge of the physical-mechanical properties of clayeysandy soils in central Italy, but may also be someway useful in road engineering applications.